1997
DOI: 10.1016/s0954-6111(97)90254-7
|View full text |Cite
|
Sign up to set email alerts
|

Thickness of the basement membrane of bronchial epithelial cells in lung diseases as determined by transbronchial biopsy

Abstract: The thickness of the basement membranes of bronchial epithelial cells varies under various pathological conditions. It has been reported that this membrane is thickened in patients with bronchial asthma. By light microscopy, this parameter was measured in biopsy specimens of bronchial mucosa obtained by fibre-optic bronchoscopy. These specimens were obtained from 171 patients who had undergone bronchial biopsy between 1984 and 1994. It was demonstrated that the thickness of the basement membrane of bronchial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 9 publications
3
24
0
Order By: Relevance
“…T1DM is associated with reduced lung capacities, elastic recoil, and dynamic lung compliance (55,57), likely a consequence of increased collagen cross-linking in the lung and thorax (9). Autopsy of diabetic lung tissue shows basement membrane thickening (32,73) including alveolar epithelium and capillary endothelium basal lamina (72,77). In streptozotocin-induced T1DM, the volume of alveolar wall is increased due to higher contents of collagen, elastin, and basal laminae (31,42,51), which partially result from slower degradation of connective tissue (43).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…T1DM is associated with reduced lung capacities, elastic recoil, and dynamic lung compliance (55,57), likely a consequence of increased collagen cross-linking in the lung and thorax (9). Autopsy of diabetic lung tissue shows basement membrane thickening (32,73) including alveolar epithelium and capillary endothelium basal lamina (72,77). In streptozotocin-induced T1DM, the volume of alveolar wall is increased due to higher contents of collagen, elastin, and basal laminae (31,42,51), which partially result from slower degradation of connective tissue (43).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Remodelling of the airway wall has been assessed using bronchial biopsy specimens (3,(7)(8)(9)(10)(11)(12)(13) as well as inflammatory changes of airway using high resolution computed tomography (HRCT) (14)(15)(16)(17)(18)(19). The assesment using HRCT technique involved radiation risk and is not applicable for bronchial mural structure.…”
Section: Introductionmentioning
confidence: 99%
“…Major alterations found in the airways of asthmatics are thickened basement membrane [18,19] and bronchial vessel dilation (reviewed by [20]). The authors found that there was a significant change in the thickness of the basement membrane after epithelial damage to the rat trachea that was due to the disruption of the TJ.…”
Section: Discussionmentioning
confidence: 99%